2019
DOI: 10.2106/jbjs.18.00417
|View full text |Cite
|
Sign up to set email alerts
|

No Difference in Outcomes Detected Between Decellular Nerve Allograft and Cable Autograft in Rat Sciatic Nerve Defects

Abstract: Background: Nerve injuries with a gap/defect represent a clinical challenge without a clear solution. Reconstruction with cable autografts is a common treatment technique, and repair with decellular nerve allograft is a newer option. The purpose of this study was to compare the functional outcomes of reconstruction with cable autografts with those of matched-diameter decellular nerve allografts to evaluate the relative importance of diameter as well as the autograft-versus-allograft nature of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…The reverse-polarity autograft is not the clinical gold standard; however, we were unable to use sural autograft due to the aforementioned limitations and chose to use the reverse-polarity autograft, which is the predominant positive control used in both small animal and large animal nerve defect studies (46,(70)(71)(72). Furthermore, Tang et al (73) recently demonstrated that there was no significant difference in performance of the sural nerve autograft versus reverse-polarity nerve autograft in a rat sciatic nerve defect model, further justifying the use of the reverse-polarity autograft as a clinical control.…”
Section: Discussionmentioning
confidence: 99%
“…The reverse-polarity autograft is not the clinical gold standard; however, we were unable to use sural autograft due to the aforementioned limitations and chose to use the reverse-polarity autograft, which is the predominant positive control used in both small animal and large animal nerve defect studies (46,(70)(71)(72). Furthermore, Tang et al (73) recently demonstrated that there was no significant difference in performance of the sural nerve autograft versus reverse-polarity nerve autograft in a rat sciatic nerve defect model, further justifying the use of the reverse-polarity autograft as a clinical control.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the clinical literature, given the potential for increased OR time and the need for a harvest site for autograft nerve repair procedures. 5,11,14 There was no significant difference in mean R&B cost between autograft and allograft nerve repair procedures with average costs directionally lower, although not statistically significant, for allograft nerve repairs. The Lans et al study reported lower total costs of care for allograft versus autograft repair in the inpatient setting ($25,751 and $29,560 respectively) and similar costs for allograft versus autograft repair in outpatient settings ($13,143 and $12,635, respectively) from an analysis of the 2018 Medicare Standard Analytic File.…”
Section: Discussionmentioning
confidence: 88%
“…Introduced into clinical practice in 2007, nerve allograft includes the potential for reduced operative time, avoiding additional risks associated with the donor site (such as neuroma formation or infection), the use of regional rather than general anesthesia, 11,12 and off-the-shelf availability (in 15 mm to 70 mm length, and 1-2 mm to 4-5 mm diameter), contributing to ease of use. 12,14,15 In a published meta-analysis comparing meaningful recovery rates and postoperative complications after autograft, allograft, and conduit repair in nerve gaps greater than 5 mm and less than 70 mm, overall meaningful recovery for sensory and motor function was not significantly different between autograft and allograft across both short and long gaps. Meaningful recovery rates for autograft (81.6%) and allograft (87.1%) repairs were significantly higher compared with conduits (62.2%) in sensory short gap repairs (nerve gaps 5-30 mm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 This study and others have demonstrated that isometric tetanic force is a reliable technique in determining the degree of functional recovery of a reinnervated muscle as a direct measure of reinnervation. 5,[44][45][46] Electrophysiologic outcomes tended to be superior in the allograft wrapped in superficial inferior epigastric artery fascial flap group compared to nerve allograft alone. As compound muscle action potential is greatly affected by factors such as changes in temperature and electrode location, there is greater variability than isometric tetanic force data.…”
Section: Discussionmentioning
confidence: 96%